Nucleation kinetics assessment for carbamazepine co-crystals crystallised - S., Abd Rahim; R., B. Hammond; K., J. Roberts; A., Y. Sheikh (2016)
In previous years, studies have been conducted involving carbamazepine (CBZ) including screening of co-crystal formation with a range of co-crystal formers using various screening methods, identifying the bonding synthon type occurring in the structures and also examining the physical and/or chemical properties improvement of the co-crystal compared to CBZ in its pure form. However, not much was reported about the kinetics of this co-crystal. Thus, in this paper, the findings of nucleation kinetics for CBZ co-crystals w ith co-crystal formers namely succinic acid (SCA), aspirin (ASP) and saccharine (SAC) obtained from slow cooling crystallisation are discussed. The slow cooling experiments were conducted to find MSZW and nucleation order from Nyvlt equation